PACAP regulates VPAC1 expression, inflammatory processes and lipid homeostasis in M1- and M2-macrophages - Witzel, Roman; Block, Annika; Pollmann, Solvey; Oetzel, Leandra; Fleck, Fenja; Bonaterra, Gabriel A.; Kinscherf, Ralf; Schwarz, Anja (Frontiers in Cardiovascular Medicine, 2023)
Background: Pituitary adenylate cyclase-activating polypeptide (PACAP) acts as an anti-atherogenic neuropeptide and plays an important role in cytoprotective, as well as inflammatory processes, and cardiovascular regulation. Therefore, the aim of this study is to investigate the regulatory effects of PACAP and its receptor VPAC1 in relation to inflammatory processes and lipid homeostasis in different macrophage (MΦ) subtypes. Methods: To investigate the role of PACAP deficiency in the pathogenesis of atherosclerosis under standard chow (SC) or cholesterol-enriched diet (CED) in vivo, PACAP-/- mice were crossbred with ApoE-/- to generate PACAP-/- / ApoE-/- mice. Lumen stenosis in the aortic arch and different MΦ-subtypes were analyzed in atherosclerotic plaques by quantitative immunohistochemistry. Undifferentiated bone marrow-derived cells (BMDC) from 30-weeks-old ApoE-/- and PACAP-/- / ApoE-/- mice were isolated, differentiated into BMDM1- and BMDM2-MΦ, and incubated with oxidized low-density lipoprotein (oxLDL). In addition, PMA-differentiated human THP-1 MΦ were further differentiated into M1-/M2-MΦ and subsequently treated with PACAP38, the VPAC1 agonist ([Ala11,22,28]VIP), the antagonist (PG 97-269), and/or oxLDL. Uptake/accumulation of oxLDL was analyzed by oxLDL-DyLightTM488 and BodipyTM 493/503. The mRNA expression was analyzed by qRT-PCR, protein levels by Western blot, and cytokine release by ELISA. Results: In vivo, after 30 weeks of SC, PACAP-/- / ApoE-/- mice showed increased lumen stenosis compared with ApoE-/- mice. In atherosclerotic plaques of PACAP-/- / ApoE-/- mice under CED, immunoreactive areas of VPAC1, CD86, and CD163 were increased compared with ApoE-/- mice. In vitro, VPAC1 protein levels were increased in PACAP-/- / ApoE-/- BMDM compared with ApoE-/- BMDM, resulting in increased TNF-α mRNA expression in BMDM1-MΦ and decreased TNF-α release in BMDM2-MΦ. Concerning lipid homeostasis, PACAP deficiency decreased the area of lipid droplets in BMDM1-/M2-MΦ with concomitant increasing adipose differentiation-related protein level. In THP-1 M1-/M2-MΦ, the VPAC1 antagonist increased the uptake of oxLDL, whereas the VPAC1 agonist decreased the oxLDL-induced intracellular triglyceride content. Conclusion: Our data suggest that PACAP via VPAC1 signaling plays an important regulatory role in inflammatory processes in atherosclerotic plaques and in lipid homeostasis in different MΦ-subtypes, thereby affecting foam cell formation. Therefore, VPAC1 agonists or PACAP may represent a new class of anti-atherogenic therapeutics.